Thermally Robust Orange‐Red‐Emitting Color Converters for Laser‐Driven Warm White Light with High Overall Optical Properties. Issue 6 (25th March 2022) - Deng, Taoli; Huang, Linhui; Li, Shuxing; Zhu, Qiangqiang; Wang, Le; Takeda, Takashi; Hirosaki, Naoto; Xie, Rong‐Jun
Abstract: Laser‐driven solid‐state lighting with super‐brightness and compactness is recognized as a promising alternative to white light‐emitting diodes. However, it is quite difficult to achieve laser‐driven warm white light with long‐term stability due to the shortage of robust orange‐ or red‐emitting laser phosphors. In this work, an efficient and thermally robust orange‐red (La, Y)3 Si6 N11 :Ce 3+ (LYSN)‐BN phosphor‐in‐glass (PiG) film is proposed to realize warm white light, where h ‐BN acts as an optical medium to enhance light scattering, a heat sink to reduce the temperature, and a protective layer to prevent LYSN from oxidation. The "LYSN+15 wt.% BN" PiG film shows an internal quantum efficiency of 70% and a luminance saturation threshold of 12.82 W mm −2, much higher than those without h ‐BN (i.e., 57.5% and 7.63 W mm −2 ). A warm white light lamp fabricated by combining "LYSN+15 wt.% BN" PiG film with blue laser diodes, showing tunable correlated color temperatures (2800–5000 K), has a maximal luminous flux of 740 lm and a luminous efficacy of 133.5 lm W −1, which promises high collimation and penetration lighting in the rainy or foggy weather. By designing a composite orange‐red‐emitting phosphor converter, this work lays a foundation for realizing high quality laser‐driven warm white lighting source. Abstract : The laser‐driven warm white light can be created from a thermally robust orange‐red (La, Y)3 Si6 N11 :Ce 3+ ‐BN phosphors in glass film, producing an interesting microstructure that allows to regulate the light path in the film and enhance its overall optical properties. It demonstrates high collimation and long‐distance lighting in rainy or foggy weather.